Evaluating the role of Bacillus amyloliquefaciens QST 713 as a Plant Growth Promoting Rhizobacteria. - Hunt, Annabel (2019)
Due to an increasing need for sustainable crop management solutions, the use of biostimulants in agriculture is becoming much more widely researched. This study investigated the potential of Bacillus amyloliquefaciens strain QST 713 (Serenade ASO®) to promote growth of carrot and potato crops. Multiple controlled environment experiments were carried out using a variety of application methods, and different temperature regimes were also used to assess the effect of lower temperatures on bacterial growth both in vitro and in vivo. qPCR analysis was used to assess the ability of B. amyloliquefaciens to colonise potato and carrot root systems. After 28 days of potato growth, treatment with B. amyloliquefaciens resulted in a significant increase in root surface area (P= 0.045) and shoot height (P=0.047), as well as an increase in nutrient uptake. Bacillus amyloliquefaciens did not promote carrot growth at 20/15oC or 20/10oC after 21, 37 or 70 days of growth. However, when carrots were grown under a cooler temperature regime (15oC/10oC), B. amyloliquefaciens appeared to improve carrot root system development and nutrient uptake. Under the lower temperature regime, carrot root colonisation by B. amyloliquefaciens was superior to that observed under the warmer conditions (20oC/10oC). Enhanced root colonisation may have been due to the slower carrot growth rate and may explain the growth promotion effect observed under the cooler temperature regime. Results suggest B. amyloliquefaciens QST 713 could be an effective biostimulant for potato crops, but further research should investigate any yield benefits and the most efficient application method. Results also suggest that further research should investigate the potential for B. amyloliquefaciens QST 713 to alleviate against cold stress in crops.